Six new species of Begonia (Begoniaceae) from Central Sarawak, Borneo - Sang, Julia; Kiew, Ruth; Yiing, Ling Chea (Phytotaxa, 2016)
Six new species of Begonia, Begonia armykapii S.Julia & C.Y.Ling, Begonia baikoides S.Julia & C.Y.Ling, Begonia papulifolia S.Julia & C.Y.Ling, Begonia rubrobracteolata S.Julia & C.Y.Ling, Begonia tinjanii S.Julia and Begonia triangularis Kiew & C.Y.Ling, are described from the forest areas in central part of Sarawak. All species belong to the sect. Petermannia.